"Bring in an Honest Verdict": Prosecuting Southern Whiteness in American Slavery As It Is. Issue 5 (20th October 2017) - Trudeau, Justin Thomas; Morrissey, Megan Elizabeth
ABSTRACT: Acting as prosecutor and naming his public as jurors, Theodore Dwight Weld brutally makes a case against the institution of slavery in the United States in his text, American Slavery As It Is: Testimony of a Thousand Witnesses . We argue that Weld's performative rhetoric reveals both the form and content of national (northern) whiteness by means of its judicial condemnation of the slaveholding South. By contrasting southern slaveholders' lawlessness, emotional ineptitude, and lack of self-control with the reserved discipline of the North, we suggest that Weld's text enacts enduring ideological boundaries between national (northern) whiteness and southern, slaveholding whiteness.